KEBIJAKAN EKONOMI INTERNASIONAL : KEBIJAKAN PROMOSI EKSPOR DAN SUBSTITUSI IMPOR - PUPUT DWI PUSPITA SARI; Sarpini Sarpini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
International economic policy is one of the main instruments used by governments to strengthen national competitiveness in a rapidly changing global environment. Two major policy approaches that are often implemented, especially in developing countries, are export promotion policies and import substitution policies. Export promotion focuses on encouraging domestic industries to enter international markets by providing incentives, improving product quality, and expanding market access. Meanwhile, import substitution encourages countries to reduce dependence on imported goods by building strong domestic production capacities. This paper provides a comprehensive explanation of the concepts, objectives, mechanisms, and impacts of both policies. It discusses how export promotion can stimulate foreign exchange earnings, encourage innovation, and integrate domestic industries into global value chains. Likewise, it explores how import substitution can strengthen national industries, reduce vulnerabilities to external shocks, and create employment opportunities. The paper also highlights the limitations of each approach, such as the possibility of inefficiency in protected industries under import substitution or the risk of overreliance on global markets under export promotion. Furthermore, it emphasizes that many countries today successfully combine the two strategies in a balanced manner to achieve sustainable and long-term economic development. Ultimately, the effectiveness of these policies depends on institutional capacity, industrial readiness, and the alignment of policies with broader national development goals.